The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/nl8033174
|View full text |Cite
|
Sign up to set email alerts
|

Role of Polyethylene Glycol Integrity in Specific Receptor Targeting of Carbon Nanotubes to Cancer Cells

Abstract: We demonstrate that dispersion of single walled carbon nanotubes (SWNTs) by ultrasonication with phospholipid-polyethylene glycol (PL-PEG) fragments it, thus interfering with its ability to block nonspecific uptake by cells. However, unfragmented PL-PEG promoted specific cellular uptake of targeted SWNTs to two distinct classes of receptors expressed by cancer cells. Since fragmentation is a likely consequence of ultrasonication, a technique commonly used to disperse SWNTs, this maybe a concern for certain app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 37 publications
(94 reference statements)
1
71
0
Order By: Relevance
“…Simulations showed that PEGylated SWNTs penetrated into the lipid bilayer slower than unPEGylated SWNTs. Also, penetration of the PEGylated SWNT showed a less energy-dependent mechanism, indicating lower adhesion energy, which favorably compared with their previous experiments [178].…”
Section: Pegylated Lipidssupporting
confidence: 66%
“…Simulations showed that PEGylated SWNTs penetrated into the lipid bilayer slower than unPEGylated SWNTs. Also, penetration of the PEGylated SWNT showed a less energy-dependent mechanism, indicating lower adhesion energy, which favorably compared with their previous experiments [178].…”
Section: Pegylated Lipidssupporting
confidence: 66%
“…Moreover, SWCNTs have been shown to enter mammalian cells Chin et al, 2007;Kam et al, 2004;Kostarelos et al, 2007) and due to their promising properties, SWCNT-based materials have already been investigated as potential delivery vehicles for intracellular transport of nucleic acids Pantarotto et al, 2004), proteins (Kam et al, 2004; and drug molecules Chen et al, 2008;. SWCNTs have been functionalized with antibodies and low-molecular-weight targeting agents, providing high efficiency for nanotube internalization into cells Bottini et al, 2006;Cato et al, 2008, Singh et al, 2005Kang et al, 2008;Shao et al, 2007;Welsher et al, 2008;Zeineldin et al, 2009).These systems also have higher loading capacity and allow for the incorporation of targeting agents and stealth molecules may also be added to evade the immune system. (Mu et al, 2009;Heister et al,2009) Such systems have been loaded with drug molecules such as doxorubicin (DOX) via p-p stacking interactions, methotrexate, Paclitaxel and quercetin.…”
Section: Carbon Nanotubes and Their Impor-tance In Anticancer Drug Dementioning
confidence: 99%
“…Nevertheless, the first generation SWCNTs proved to be unsuitable as drug delivery vectors as they tended to form bundles that disperse poorly in aqueous solutions and were therefore unsuitable for pharmacological use. To overcome this drawback, synthetic polymers such as poly(phenylacetylene) (Zeineldin et al, 2009, Yuan et al, 2006 and natural polymers such as polysaccharides Yuan et al, 2006;Abarrategi et al, 2008;Fu et al, 2007;Hasegawa et al, 2004;Long et al, 2008;Numata et al, 2004;Zhang et al, 2008) have been used to encase SWCNTs via non-covalent interactions, thereby improving their compatibility with water and physiological environments.…”
Section: Carbon Nanotubes and Their Impor-tance In Anticancer Drug Dementioning
confidence: 99%
“…Single-walled carbon nanotubes (SWNTs) have received considerable research attention due to their many potential applications [1,2].…”
Section: Introductionmentioning
confidence: 99%